One-Year Old Dormant, “Non-culturable” Mycobacterium tuberculosis Preserves Significantly Diverse Protein Profile - Trutneva, Kseniya A.; Shleeva, Margarita O.; Demina, Galina R.; Vostroknutova, Galina N.; Kaprelyans, Arseny S. (Frontiers in Cellular and Infection Microbiology, 2020)
For adaptation to stressful conditions, Mycobacterium tuberculosis (Mtb) is prone to transit to a dormant, non-replicative state, which is believed to be the basis of the latent form of tuberculosis infection. Dormant bacteria persist in the host for a long period without multiplication, cannot be detected from biological samples by microbiological methods, however, their “non-culturable” state is reversible. Mechanisms supporting very long capacity of mycobacteria for resuscitation and further multiplication after prolonged survival in a dormant phase remain unclear. Using methods of 2D electrophoresis and MALDI-TOF analysis, in this study we characterized changes in the proteomic profile of Mtb stored for more than a year as dormant, non-replicating cells with a negligible metabolic activity, full resistance to antibiotics, and altered morphology (ovoid forms). Despite some protein degradation, the proteome of 1-year-old dormant mycobacteria retained numerous intact proteins. Their protein profile differed profoundly from that of metabolically active cells, but was similar to the proteome of the 4-month-old dormant bacteria. Such protein stability is likely to be due to the presence of a significant number of enzymes involved in the protection from oxidative stress (katG/Rv1908, sodA/Rv3846, sodC/Rv0432, bpoC/Rv0554), as well as chaperones (dnaJ1/Rv0352, htpG/Rv2299, groEL2/Rv0440, dnaK/Rv0350, groES/Rv3418, groEL1/Rv3417, HtpG/Rv2299c, hspX/Rv2031), and DNA-stabilizing proteins. In addition, dormant cells proteome contains enzymes involved in specific metabolic pathways (glycolytic reactions, shortened TCA cycle, degradative processes) potentially providing a low-level metabolism, or these proteins could be “frozen” for usage in the reactivation process before biosynthetic processes start. The observed stability of proteins in a dormant state could be a basis for the long-term preservation of Mtb cell vitality and hence for latent tuberculosis.